2015
DOI: 10.1182/blood-2014-05-575225
|View full text |Cite
|
Sign up to set email alerts
|

T-cell–restricted T-bet overexpression induces aberrant hematopoiesis of myeloid cells and impairs function of macrophages in the lung

Abstract: Key Points• Mice overexpressing T-bet in T cells show aberrant hematopoiesis of myeloid cells and functional conversion of regional macrophages.• The mice developed a severe PAP-like disease with a hematopoietic disorder resembling the human disease.Although overexpression of T-bet, a master transcription factor in type-1 helper T lymphocytes, has been reported in several hematologic and immune diseases, its role in their pathogenesis is not fully understood. In the present study, we used transgenic model mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 63 publications
1
15
0
1
Order By: Relevance
“…It has recently been reported that hyperactivation of Th1 cells causes PAP. In this model, the expression of Bach2 is increased in AMs (36). This observation is consistent with a role of Bach2 in restricting responses to inflammation.…”
Section: Alveolar Macrophage Identity Crisis In Bach2-deficient Micesupporting
confidence: 89%
“…It has recently been reported that hyperactivation of Th1 cells causes PAP. In this model, the expression of Bach2 is increased in AMs (36). This observation is consistent with a role of Bach2 in restricting responses to inflammation.…”
Section: Alveolar Macrophage Identity Crisis In Bach2-deficient Micesupporting
confidence: 89%
“…However, these observations suggest overlapping pathophysiologic pathways between MAS and SJIA‐LD, in which the inflammatory cytokine milieu that drives MAS also promotes alveolar macrophage dysfunction (Figure ). Consistent with this hypothesis, mice with T cell–restricted overexpression of T‐bet driving IFNγ production demonstrated both dysfunction of bone marrow macrophages, resulting in erythrophagocytosis, and dysfunction of alveolar macrophages with development of PAP‐like lung pathology ().…”
Section: Discussionmentioning
confidence: 78%
“…The results identified a novel mechanism by which increased expression of T-bet, exclusively in T lymphocytes, spontaneously drives the pathogenesis of both MDS and secondary PAP in a dose-dependent manner. [ 20 ] In this report, 1 case developed secondary PAP happened at the same time as MDS, and the other occurs after MDS. We speculate that the functional impairment of mononuclear phagocytes in the lung associated with aberrant hematopoiesis of myeloid cells might account for the development of secondary PAP in our patients.…”
Section: Discussionmentioning
confidence: 71%